Effect of tanniniferous plants and essential oils on methane emission in ruminants - Rahman, Yosra Ahmed Soltan Abd El (2012)
Tannins and essential oils are secondary metabolites that may be used as natural modifiers of rumen fermentation to reduce the ruminants\' methane (CH4) emission. To study the application of tannin-rich plants from Egypt and Brazil, as well as essential oils that are available in international trade, three studies were conducted at Animal Nutrition Laboratory of Centro de Energia Nuclear na Agricultura, Universidade de São Paulo, at Piracicaba, Brazil. The first study was aimed to assess the potential of tanniniferous plants prosopis (Prosopis juliflora), acacia (Acasia saligna), atriplex (Atriplex halimus) and leucena (Leucaena leucocephala) in in vitro gas production assay, evaluating the methanogenic activity, ruminal fermentation, degradability and post ruminal protein digestibility compared with Tífton hay (Cynodon spp.) as non tannin feed. The ranking of the plants according to their potential to reduce CH4 based on organic matter truly degraded (OMTD) was acacia> leucena> atriplex> prosopis. Prosopis and leucena presented greater (P=0.002) propionate (C3) production with corresponding decrease (P=0.004) in the acetate:propionate ratio (C2/C3). Acacia and leucena showed lower (P=0.0002) NH3-N concentration associated with the decline in protein ruminal degradability. However, leucena showed greater (P<0.001) intestinal protein digestibility than acacia. The objective of the second study was to evaluate in vitro the potential of constituents of essential oils carvacrol (CAR) and eugenol (EUG) at doses of 5, 10 and 20 (CAR) and 10, 20 and 30 (EUG) \'mü\'l/75ml of culture fluid, as a natural alternative to rumen microbial fermentation modifiers compared with monensin (MON) (3 \'mü\'M/75ml of culture fluid) as a positive control. CAR10 and EUG20 showed similarity (P>0.05) in reduction of CH4 emission and OMTD compared with MON, but it had different (P<0.05) short chain fatty acids (SCFA) profile. Monensin increased C3 concentration and decreased C2/C3 ratio, but CAR10 and EUG20 increased (P<0.0001) concentrations of butyrate without effect on the total SCFA. Leucena was selected in the third study to evaluate in vivo the tannins biological activity in total apparent digestibility, nitrogen balance, rumen fermentation and CH4 emission. Six adult rumen cannulated Santa Inês sheep (70±2.5 kg) were individually divided into three experimental diets in a double Latin square design (3 treatments, 3 periods, 6 animals). In the control diet (CNTRL), animals received a basal diet containing Tifton hay (70%), soybean meal (21%) and ground maize (9%). The second diet contained leucena (LEUC), (123 and 8.8 g/kg DM of total tannins and condensed tannins respectively) replacing 50% of Tífton hay. The third diet (LPEG), polyethylene glycol was supplemented at rate of 20g/day/animal. Leucaena-containing diets increased intake of crude protein (P=0.008) and lignin (P<0.001) compared with CNTRL, while there were no significant differences among all diets for the nutrients apparent digestibility except for acid detergent fiber (ADF) was reduced (P=0.0009) by LEUC. Leucaena-containing diet reduced (P<0.001) rumen ammonia concentration and urinary excretion of nitrogen (P=0.0065). Leucena-containing diets decreased (P<0.001) CH4 emission as well as reduced (P<0.001) C2/C3 ratio compared to CNTRL. These studies highlight the potential of tanniniferous plants and the essential oils active components to modulate the rumen fermentation and to reduce CH4 emission in ruminants